Development of Student Worksheets on Static Electricity Material to Identify Higher Order Thinking Skill (HOTS) - Rasyid, M.; Unayah, H.; Iqdami, N.; Nurohman, S. (Universitas Negeri Yogyakarta, 2025)
This study examined the design of learning materials based on Android, using both static and dynamic electricity. It created educational materials that include electrical components, both static and dynamic but are invisible to the human eye. The study aimed to determine the viability of producing Student Worksheets Based on Higher-Order Thinking Skills (HOTS) on Static Electricity Material and making a product based on HOTSs on static electricity. The 4D (Four D Model) development model from Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel that is, defining, planning, developing, and disseminating is used in this work in conjunction with the Research and Development (R&D) technique. The experts in materials and media conducted validation through an evaluation form to measure the product's viability. Two phases of the experiment were conducted: field trials and restricted trials. Based on Higher Order Thinking Skills (HOTS) information on static electricity, student worksheets for physics instruction have been created using a 4D stage model: define, design, develop, and disseminate. After going through several phases of validation with media experts, material experts, and trials, the instructional materials were deemed acceptable and fit for students. The student worksheets produced teachers' feedbacks received an average score of 88% in the